Early Human Migrations (ca. 13, 000 Years Ago) or Postcontact Europeans for the Earliest Spread of Mycobacterium leprae and Mycobacterium lepromatosis to the Americas. (9th November 2017) - Mark, Samuel
Abstract : For over a century, it has been widely accepted that leprosy did not exist in the Americas before the arrival of Europeans. This proposition was based on a combination of historical, paleopathological, and representational studies. Further support came from molecular studies in 2005 and 2009 that four Mycobacterium leprae single-nucleotide polymorphisms (SNPs) and then 16 SNP subtypes correlated with general geographic regions, suggesting the M. leprae subtypes in the Americas were consistent with European strains. Shortly thereafter, a number of studies proposed that leprosy first came to the Americas with human migrations around 12, 000 or 13, 000 years ago. These studies are based primarily on subsequent molecular data, especially the discovery of a new leprosy species Mycobacterium lepromatosis and its close association with diffuse lepromatous leprosy, a severe, aggressive form of lepromatous leprosy, which is most common in Mexico and the Caribbean Islands. A review of these and subsequent molecular data finds no evidence for either leprosy species in the Americas before the arrival of Europeans, and strains of both species of leprosy found in eastern Mexico, Caribbean Islands, and Brazil came from Europe while strains found in western Mexico are consistent with their arrival via direct voyages from the Philippines.